Newly developed genomic SSR markers revealed the population structure and genetic characteristics of abaca (Musa textilis Nee) - Mariecris Rizalyn R. Mendoza; Antonio C. Laurena; Maria Genaleen Q. Diaz; Eureka Teresa M. Ocampo; Tonette P. Laude; Antonio G. Lalusin (BioTechnologia)
Abaca ( Musa textilis Nee) is the primary source of manila hemp fiber, a vital industrial product for the country. Previous studies have relied on molecular markers designed for other Musa species or distant genera like rice, limiting accurate genetic characterization and germplasm conservation. To address this, we developed 50 genome-specific molecular markers based on the recently released whole genome sequence assembly of Abaca var. Abuab by Galvez et al. (2021). Among these markers, 28 showed high polymorphism, with an average PIC value of 0.78. Population analysis revealed a heterozygosity of 0.428, indicating moderate genetic diversity, supported by an alpha value of 0.0735 and an F stp value of 0.0815, which suggests moderate genetic differentiation among abaca accessions. Cluster analyses, generated by DARwin and STRUCTURE software with 91% similarity, identified four clusters. The new markers were also able to distinguish six Musa accessions exhibiting morphological traits of both abaca and banana. Discrepancies in sample identification due to identical or inverted names were resolved using population structure analysis. Molecular variance analysis showed a 12% variance among the four abaca subpopulations and 88% within populations, suggesting recent divergence. Our study highlights the diversity, identity, and genetic variation within the abaca collection using accurate, robust, cost-effective, and computationally simple genome-specific markers. These markers are pivotal for genetic studies of abaca, including trait-marker mapping and the differentiation of accessions even in the juvenile stage, when phenotypic differences may be subtle.